The Correlation Between School Climate and Teacher Job Satisfaction at Inclusive School in Martapura - Karyati, Faridah; Ariani, Alpha; Astuti, Nadya (IJBLE Scientific Publications Community Inc., 2025)
This study aimed to explore the school climate at SMK Negeri 1 Martapura, assess the level of teacher job satisfaction, and examine the correlation between school climate and teacher job satisfaction. A survey method with a correlation approach was employed, using questionnaires distributed to 25 teachers at SMK Negeri 1 Martapura as respondents. To collect data on variables X (school climate) and Y (teacher job satisfaction), a Likert-scale questionnaire was used as the research instrument. The results of this study indicated that teachers perceive their school climate as an open type; however, the intimacy dimension remains relatively low. In addition, many teachers at SMK Negeri 1 Martapura reported a moderate level of job satisfaction. The product-moment correlation coefficient test yields a count of 0.612, which is greater than the table of 0.396 at a 5% significance level. This demonstrates a positive correlation between school climate and teacher job satisfaction.